STUDY AND ANALYSIS OF IMPLEMENTING INNOVATIVE TECHNOLOGY IN ENGINEERING EDUCATION FOR CREATING PRODUCTIVE LEARNING ENVIRONMENT - Krishnasamy, Hariharan N; Kumar, N. Ashok Kumar; Soliman, Karim; Haque, Rasheedul; Guechi, Ryma; Senathirajah, Abdul Rahman Bin S. (Journal of Posthumanism, 2025)
The goal of innovation technology is to make certain that each and every student is provided with an education that is of the highest possible calibre, is distributed fairly, and is welcoming to everyone. The use of digital technology has emerged as an essential resource for reaching this objective in recent years. The use of these technologies permits the localization of emission sources, the reduction of environmental harm via the introduction of alternatives to fossil fuels that are both energy-efficient and low-carbon, and the possible extraction of surplus greenhouse gases from the atmosphere. The use of digital technology should result in an increase in production and efficiency while simultaneously reducing or eliminating waste and pollution as much as possible. It has been noted that the educational system is being significantly impacted by these technological advancements. The COVID-19 epidemic has resulted in an increased focus on the incorporation of digital technology into the curriculum of educational institutions. The paradigm of the educational system has undergone a considerable transformation as a direct result of the incorporation of digital technology. In addition to being responsible for the transmission of information, the person in question is also expected to act as a guide, an assessor, and a collaborator in the process of the development of new knowledge. Students' day-to-day lives have become less complicated as a direct result of the development of new educational technologies. In today's world, students are more likely to produce presentations and projects with the assistance of a variety of software and tools than they are with the use of conventional writing instruments. When compared to the weight of a stack of notebooks, the iPad's heft is much more manageable.